New records of Cassidinae and Cerambycidae (Coleoptera: Chrysomeloidea) from Baturité Massif, Brazil, with the description of a new species of Charidotis (Coleoptera: Chrysomelidae: Cassidinae) - Simões, Marianna V. P.; Sekerka, Lukáš; Mota, Adriana Andrade; Nearns, Eugenio H.; Monné, Miguel A.; Monné, Marcela L. (Zootaxa, 2024)
The Baturité massif, situated in Ceará state’s central hinterland, is one of the largest humid mountain ranges in the Brazilian semi-arid region. Flora and vertebrate surveys have been conducted in the region, revealing endemic species, as well as a combination of fauna and flora from neighboring biomes, the Atlantic and Amazon rainforests. However, invertebrate inventories have been scarce, leaving a significant portion of the region’s biodiversity unexplored. This paper presents the outcomes of collaborative expeditions conducted by the recently established Museu de História Natural do Ceará Prof. Dias da Rocha and Museu Nacional/Universidade do Rio de Janeiro to fill this knowledge gap by promoting surveys to document the region’s biodiversity. As a result, one new species of tortoise beetle is described from the massif, Charidotis rochai Simões and Sekerka, new species. Additionally, we report thirteen new state records for the beetle subfamilies Cassidinae (Chysomelidae), and Cerambycinae and Lamiinae (Cerambycidae). Among these records, eight genera are documented for the first time in the state of Ceará, and the species Centrocerum variatum (Newman, 1841) constitutes the first record in the northeastern region of Brazil. These findings underscore the significance of survey initiatives and the need for comprehensive biodiversity study within the Baturité massif.